Improving the Ability to Understand Building Spaces through the Use of Visual Media for Grade V Students of SDN Kolor II - Ikra Mulyadi, Veri (LP2M IAI Al-Khairat Pamekasan, 2025)
This study was motivated by the low academic performance of students in mathematics, particularly in the topic of solid geometry, which requires strong visualization and spatial reasoning skills. The purpose of this research is to investigate the extent to which the use of visual media can enhance the mathematics learning outcomes of fifth-grade students at SDN Langsar I. The research employed a Classroom Action Research (CAR) approach conducted over two cycles, with each cycle consisting of planning, action implementation, observation, and reflection stages. The results of the study indicated a significant improvement in students' learning outcomes following the implementation of visual media in the learning process. In the pre-action phase, only 3 students met the Minimum Mastery Criteria (MMC). After the implementation of Cycle I, the number of students who achieved mastery increased to 7 students, representing 43.75% of the class. A more substantial improvement was observed in Cycle II, where 14 students, or 87.5%, successfully met the MMC. These findings demonstrate that the integration of visual media such as images, 3D models, and other visual aids has a positive impact on students' conceptual understanding and academic achievement in learning solid geometry. Therefore, visual media can be considered an effective alternative teaching strategy to improve the quality of mathematics instruction at the elementary school level.